Um Modelo de negociação de Serviços com QoS Fim-a-Fim na Internet - Pedatella, Rodrigo N.; Madeira, Edmundo R. M.; Magalhães, Maurício (Journal of Communication and Information Systems, 2017)
Considering the increasing Internet popularity as an important communication vehicle, the acquirement of Quality of Service (QoS) represents an eminent necessity. Consequently, the study of solutions that can make this environment suitable for the traffic of applications that demand QoS have received great attention. In this context, automatic and dynamic negotiation of services presents great importance since it certainly contributes in acquiring the necessary QoS to the current applications. This paper proposes the specification of a service negotiation model for use in the Internet which is intended to be capable of supporting endto-end transmissions with QoS requirements.